Serological Tests Do Not Predict Residual Fibrosis in Hepatitis C Cirrhotics with a Sustained Virological Response to Interferon - D’Ambrosio, Roberta; Degasperi, Elisabetta; Aghemo, Alessio; Fraquelli, Mirella; Lampertico, Pietro; Rumi, Maria Grazia; Facchetti, Floriana; Grassi, Eleonora; Casazza, Giovanni; Rosenberg, William; Bedossa, Pierre; Colombo, Massimo (PloS one, 2016)
Liver biopsy (LB) has lost popularity to stage liver fibrosis in the era of highly effective anti-hepatitis C virus (HCV) therapy, yet diagnosis of persistent cirrhosis may have important implications following HCV eradication. As performance of serological non-invasive tests (NITs) to predict residual fibrosis in non-viremic HCV patients is unknown, we investigated accuracy of NITs to predict residual fibrosis in cirrhotics after a sustained virological response (SVR) to interferon (IFN). Thirty-eight patients with a pre-treatment histological diagnosis of cirrhosis and a 48-104 months post-SVR LB were tested with APRI, CDS, FIB-4, FibroQ, Forns Score, GUCI Index, King Score, Lok Index, PLF, ELF. In 23 (61%) patients, cirrhosis had histologically regressed. All NITs values declined after SVR without any significant difference between regressors and non-regressors (AUROC 0.52-0.75). Using viremic cut-offs, PPV ranged from 34% to 100%, with lower NPV (63% - 68%). NITs performance did not improve using derived cut-offs (PPV: 40% - 80%; NPV: 66% - 100%). PLF, which combines several NITs with transient elastography, had the best diagnostic performance (AUROC 0.75, Sn 61%, Sp 90%, PPV 80%, NPV 78%). After treatment, none of the NITs resulted significantly associated with any of the histological features (activity grade, fibrosis stage, area of fibrosis). The diagnostic estimates obtained using both viremic and derived cut-off values of NITs were suboptimal, indicating that none of these tests helps predicting residual fibrosis and that LB remains the gold standard for this purpose.